Fact and factual narrative in the Belarusian literary discourse - Gubskaya, Olga N. (Journal of the Belarusian State University. Philology, 2022)
The article touches upon the issue of the communicative nature of a literary text, presents the main techniques of narratological analysis that contribute to the disclosure of a literary work as an act of communication. At the same time it is emphasised that the communicative event, and, accordingly, the communication strategies used, are broader than the narrative event of the work and narration strategies. Based on the literary works of outstanding scientists M. M. Bakhtin, Yu. M. Lotman, V. I. Tyupa the author of the article suggests an order for the study of a literary work, which analyses both discursive and narrative levels of the text. It is noted that at the end of the 20th century, a new narrative practice of processing a fact was being formed in Belarusian literature, without the need to introduce it into the discourse of an artistic word, without allegorical coverage of events. It was during the perestroika that the diary narrative and attention to fact as a self-sufficient literary element became the dominant directions of the creative process. There are all grounds to assert that the Belarusian literature of fact has been formed and it is an original phenomenon of national literature. The concept acts as a hyperonym to such a term-hyponym from the branch of poetics in literary studies as Aesop’s language. As an example of the term «Belarusian literature of fact» the work of Yanka Bryl «Mouthpiece and folder» is used. It is noted that the writer creates a three-dimensional space to reveal the fact. Firstly, he passes the real fact through the perception of the I-narrator, as close as possible to the real author, thus the real fact becomes the subject of narration. Secondly, Ya. Bryl reveals this fact not only through the prism of its perception, but also forms a picture around it, that gives panoramic coverage of the event. Thirdly, the writer collides the external and internal chronotopes of the work, demonstrating the perception of an event in time.